Adaptation of the safety criteria for research reactors in zero power reactors - application for the RA0 Reactor - Di Benedetto, A. (2020)
Fil: Di Benedetto, A. RA0 Nuclear Reactor, Comisión Nacional de Energía Atómica. Córdoba; Argentina.